Gambaran Farmakoterapi Pasien Common Cold Di Puskesmas Pekanbaru - Dimas Pramita Nugraha; Inayah Inayah (Jurnal Ilmu Kedokteran, 2016)
Common cold is still a disease with the most number of cases in Indonesia and the province of Riau in out patientswho visited the primary health center (Puskesmas). However, in primary health care, like Puskesmas and privatepractice physicians are expected pharmacotherapy common cold is not rational. Medication errors is a common problem.The purpose of this study was to determine how the use of pharmacotherapy in patients with the common cold inPuskesmas Pekanbaru. This study was an observational descriptive , with a total sample 4602 people who meet thespecified criteria .The results showed that the percentage patients common cold using symptomatic analgesic-antipyreticdrugs 70.2%.However, the percentage of patients that using antibiotics in common cold is still quite a lot (36%), alsothe use corticosteroid (17,9%) that showed medication error. The patterns pharmacotherapy of common cold inPuskesmas Pekanbaru was relatively good, but need improvement .